Teaching concepts about Integrated High School and Interdisciplinarity: case study in a Technical Course in Agricultural of the Federal Institute of Rio Grande do Sul (Research, Society and Development, 2020)
Professional education with high education formation in an integrated form needs to meet the demands of society aiming a scientific and complete education of the citizen linked to the world of work. In this educational context, the present work outlines a qualitative research of the type of case study in which we sought to verify and analyze the conceptions about the concepts of Integrated High School and Interdisciplinarity are evidenced by teachers of the Technical Course in Agricultural Integrated to High School from the Ibirubá campus of the Federal Institute of Education, Science and Technology of Rio Grande do Sul. The records were obtained from a semi-structured interview and were analyzed using a Textual Discursive Analysis. From this process, five final categories emerged, four of which are analyzed in this work, namely: i) Conceptual and methodological concepts; ii) Objectives of Integrated High School; iii) appreciation and difficulties and; iv) assumption and guidelines. It was possible to conclude that the lack of initial and continuing training, as well as the lack of reasoning, mainly methodological, are factors presented for the failure to fully implement the integration and interdisciplinarity expected for the Integrated High School. Factors such as the need to institutionalize integrated actions and teaching management that coordinate and prioritize the organization of school spaces and times were also highlighted. Many of these aspects pointed by teachers corroborate the need for an open attitude towards the object of knowledge and the importance of collective work for interdisciplinarity.